A method for recovering crystalline silicon from waste crystalline silicon solar cells using a deep eutectic solvent-hydrogen peroxide system
Through the eutectic solvent-hydrogen peroxide system, the metal silver and aluminum in crystalline silicon solar cells are gently leaching, solving the problems of silicon wafer loss and environmental pollution caused by the use of strong acids in the prior art, and achieving high efficiency and environmental protection Purity silicon wafer recycling.
Patent Information
- Application Number
- CN202410577496.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-10
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-05-10
AI Technical Summary
In the prior art, when recovering metal silver and aluminum in crystalline silicon solar cells, high concentrations of strong acids are required, resulting in silicon wafer loss and environmental pollution, and the silver leaching efficiency is low.
Using a low eutectic solvent-hydrogen peroxide system, the metal silver and aluminum are gently leached through the synergistic effect of the DES mixture of choline chloride and oxalic acid and hydrogen peroxide, thereby recovering high-purity crystalline silicon.
The efficient leaching of metal silver and aluminum was achieved, the leaching efficiency of silver was increased to 89.19%, the leaching efficiency of aluminum reached 100%, and high-purity silicon wafers were obtained without using strong acids, which had environmental protection and industrial applications. potential.
Smart Images

Figure CN118419937B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of recycling and reusing crystalline silicon solar cells, and in particular to a method for recycling crystalline silicon from waste crystalline silicon solar cells by using a low eutectic solvent-hydrogen peroxide system. Background Art
[0002] Photovoltaic energy is recognized as a new energy source to solve the fossil energy crisis and global climate change. Among various photovoltaic panels, crystalline silicon photovoltaic panels occupy the main market share. Their core components are crystalline silicon solar cells, and the valuable components of crystalline silicon solar cells are mainly silicon wafers and silver electrodes. The main process of recycling crystalline silicon solar cells includes: first removing the junction box and aluminum frame, separating the glass, crystalline silicon cells and backplane, etc., and then further recovering and separating the metal elements aluminum, silver and non-metallic elements silicon from the crystalline silicon cells, which is an important link in the closed loop of the entire recycling process. With the increase in the installed capacity of photovoltaic systems, the increasing number of discarded crystalline silicon solar cells has become an important issue of concern. Therefore, how to develop environmentally compatible and low-loss solar cell recycling and reuse technologies has become increasingly important.
[0003] In recent years, the methods for recycling crystalline silicon solar cells are mainly physical and chemical methods. Among them, physical methods mostly use multi-stage mechanical crushing and electric hydraulic crushing. Chemical methods mainly use acid-base combination or mixed acid leaching process. For example, HCl-H2O2-H2O solution (mass ratio 1:1:5) is used to remove aluminum at 80 °C, and then 5% HF and 25% NaOH are used to remove silicon nitride and silver to recover 62% of silicon (WH Huang, WJ Shin, L. Wang, WC Sun and M. Tao, Solar Energy, 2017, 144, 22-31.); for example, HF-HNO3-H2SO4-CH3COOH mixed acid and surfactant are used to remove metal electrodes, anti-reflection layers and pn junctions, and the final silicon recovery rate is 86% (S. Kang, S. Yoo, J. Lee, B. Boo and H. Ryu, RenewableEnergy, 2012, 47, 152-159.). However, the high concentration of inorganic acid (corrosive strong acid such as hydrochloric acid, sulfuric acid, nitric acid, etc.) used above will cause the loss of silicon wafers, affect their recyclability, and are not environmentally friendly. Therefore, the current main research direction should be in line with the theme of green and environmental protection, and obtain silicon wafers with less loss without using strong acid.
[0004] With the development of technology, deep eutectic solvents (DES) have been successfully applied to metal leaching and are considered to be green solvents that can replace strong acid leaching of metals. However, DES is currently mainly used for the leaching of metal oxides, while the metals on crystalline silicon solar cells are simple substances rather than metal oxides. Although there are currently related technologies for extracting various complex metals (lithium, nickel, cobalt, and manganese metals) from waste lithium-ion batteries using DES, it is still difficult to use the existing DES system to efficiently leach the metallic silver from crystalline silicon cells. Therefore, how to select a suitable DES composite system that can gently and non-destructively leach silver and aluminum, especially metallic silver, from crystalline silicon solar cells, and recycle silicon wafers in a green way without using complex additives, is a technical problem that urgently needs to be solved in the industry. Summary of the invention
[0005] The purpose of the present application is to address the deficiencies of the prior art and to provide a method for recovering crystalline silicon from waste crystalline silicon solar cells using a low eutectic solvent-hydrogen peroxide system, which achieves gentle, green and harmless, and efficient leaching of metallic silver and aluminum, thereby recovering high-purity crystalline silicon.
[0006] The above invention objectives of the present application are achieved through the following technical solutions:
[0007] The above invention objectives of the present application are achieved through the following technical solutions:
[0008] A method for recovering crystalline silicon from waste crystalline silicon solar cells using a deep eutectic solvent-hydrogen peroxide system comprises the following steps:
[0009] Step A, vacuum drying choline chloride and oxalic acid to remove moisture;
[0010] Step B, mixing the dried choline chloride and oxalic acid in a molar ratio of 1:1, placing in a water bath, controlling the temperature at 75-85° C., and stirring in the water bath until a uniform transparent liquid is formed to obtain a choline chloride-oxalic acid DES mixture, then cooling to room temperature, and storing in a dry container for standby use;
[0011] Step C, mixing a certain amount of the DES mixture of step B, hydrogen peroxide with a mass concentration of 30%, and water to form a DES-H2O2 mixed solution, and then mixing the crystalline silicon cell obtained after pretreatment with the DES-H2O2 mixed solution, and placing them in a water bath, controlling the temperature at 75-85°C, and stirring for a period of time to fully leach the metal;
[0012] Step D: After the leaching step is completed, the liquid phase and the solid phase silicon wafer are separated by vacuum filtration, the concentrations of metallic silver and aluminum in the separated leaching solution are measured, and the metal leaching rate is calculated;
[0013] Step E: The separated solid silicon wafer is first dried to remove residual moisture, then mixed with NaOH solution, and placed in a water bath at 75-85° C. with constant stirring to remove the anti-reflection layer on the front side of the silicon wafer. After filtration, a high-purity silicon wafer with a smooth surface is recovered.
[0014] Preferably, in step A, the vacuum drying temperature is 60-70° C., and the drying time is 3.5-4.5 h.
[0015] Preferably, in steps B and C, magnetic stirring is used in the water bath, and the stirring speed is 250 to 350 rpm.
[0016] Preferably, in step C, in the DES-H2O2 mixed solution, the concentration of the DES mixture is 2.0-2.5 mol / L, the concentration of hydrogen peroxide is 1.5-2.0 mol / L, the solid-liquid ratio of the waste crystalline silicon cell to the DES-H2O2 mixed solution is 1g / 100ml-1g / 125ml, and the leaching time is 110-130 min.
[0017] Preferably, in step C, the crystalline silicon cell is obtained by pre-treating the crystalline silicon photovoltaic panel, and the pre-treating step is:
[0018] First, remove the aluminum frame and junction box of the crystalline silicon photovoltaic panel, then cut the battery pack, and then perform pyrolysis in a tubular furnace. The pyrolysis conditions are: heating to 480 °C in a nitrogen environment, at a rate of 15 °C / min, and a residence time of 30 min; after pyrolysis, crystalline silicon cells, copper wires and glass are obtained.
[0019] Preferably, in step D, the separated leaching solution is diluted to 100 mL with aqueous nitric acid solution, and then filtered through a 0.22 μm membrane, and the concentrations of metallic silver and aluminum are determined by inductively coupled plasma emission spectroscopy to calculate the leaching efficiency of metallic silver and aluminum.
[0020] Furthermore, the metal leaching efficiency η Me Calculated by formula (1):
[0021] η Me = [(C Me × V) / (ω Me × m)] × 100% (1)
[0022] Among them, C Me (mg / L) is the concentration of the metal element (Me is Ag or Al);
[0023] V (L) is the volume of the leachate;
[0024] ωMe (mg / g) is the concentration of metal Me in the crystalline silicon cell;
[0025] m (g) is the weight of the crystalline silicon cell.
[0026] Preferably, in step E, the concentration of the NaOH solution is 1.0 mol / L, and the reaction time is 30-40 min.
[0027] Preferably, in step E, magnetic stirring is used in the water bath, and the stirring speed is 250 to 350 rpm.
[0028] This application has the following beneficial technical effects:
[0029] 1. In the (ChCl-OA) DES-H2O2 solution system, the leaching efficiency of metal aluminum is 100%, and the leaching efficiency of metal silver reaches 89.19%. Compared with the solution system of the prior art using only DES (the leaching efficiency of silver is 45.17%), the leaching efficiency of silver is increased by 97.45%, almost twice the effect. Its mechanism of action is: (1) Oxalic acid (OA) is miscible with water in any ratio in the DES mixture, and the solubility of oxalic acid increases, thereby increasing the acidity of the system, thereby promoting the direct leaching of silver in DES; (2) Under the catalytic action of H2O2, silver is directly oxidized and accompanied by superoxide free radicals (·O2 - ) is generated. The oxidizing property of free radicals in an acidic environment is stronger, which reduces the activation energy of silver leaching in H2O2 and further promotes the leaching of silver. (3) After the silver ions are generated, the oxalate and chloride ion ligands in the DES-H2O2 system form complexes with them, further promoting the forward leaching of silver.
[0030] 2. After the residual impurity layer (mainly Si3N4) is removed by the NaOH solution, the surface purity of the silicon wafer reaches 97.47%, the silicon retention rate reaches 99.41% (169 μm), and high-purity crystalline silicon is recovered;
[0031] 3. The method of the present invention obtains high-purity silicon wafers by efficiently leaching metals at low temperature (75-85°C) and in a short time (about 2 hours) without using strong acid, and DES has the potential to be recycled and reused and to enrich metals. Therefore, the process of the present invention for recovering crystalline silicon from waste crystalline silicon solar cells is gentle, green, harmless and efficient, and has very good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a comparison chart of the leaching efficiency of metal aluminum and silver in Examples 1 to 4.
[0033] Figure 2 Comparison of leaching efficiency of different solution systems (a), comparison of initial pH values (b), and free radical capture experiment of DES-H2O2 system (c) are shown.
[0034] Figure 3 This is the negative ion mode spectrum of the DES high-resolution mass spectrometry after the metallic silver is leached in Example 1.
[0035] Figure 4 The following are the scanning electron microscope images (a) and XPS spectra (bd) of the silicon wafers recovered in Example 1.
[0036] Figure 5 1 is a comparison chart of the battery thickness (a) and N content (b) before and after the treatment of Example 1.
[0037] Figure 6 FT-IR (a) and 1H NMR (b) spectra of DES used repeatedly in Example 1.
[0038] Figure 7 This is a scanning electron microscope image of the front surface of the silicon wafer obtained after the treatment of Example 3. DETAILED DESCRIPTION
[0039] The present application is further described in detail below in conjunction with the accompanying drawings.
[0040] Experimental Materials:
[0041] 1. Choline chloride (C5H 14 ClNO, AR, 98%), oxalic acid (H2C2O4, AR, 98%), and hydrogen peroxide (H2O2, AR, 30%) were purchased from Shanghai MacLean Biochemical Co., Ltd., Shanghai Aladdin Biochemical Technology Co., Ltd., and Guangzhou Chemical Reagent Factory, respectively.
[0042] 2. Crystalline silicon cell samples
[0043] The sample in this example is from a polycrystalline silicon photovoltaic panel (model YL330P-36b, 330 W, Yingli Group Co., Ltd.), and its technical parameters are detailed in Table 1. The front side of the polycrystalline silicon photovoltaic panel is a silver grid line (silver electrode), and the back side is an aluminum painted electrode (aluminum electrode), which is connected by tin-plated lead copper wire. The two sides of the polycrystalline silicon photovoltaic panel are laminated with glass and back sheet respectively through ethylene vinyl acetate (EVA).
[0044] Table 1. Technical parameters of polycrystalline silicon photovoltaic panels
[0045]
[0046] First, pre-treat the polycrystalline silicon photovoltaic panel. The specific steps are as follows:
[0047] First, the aluminum frame and junction box were manually removed, and then the battery pack was cut with a water jet. Each battery pack was evenly cut into 10 equal parts with a size of 78×31.2 mm. After disassembly and cutting, pyrolysis was performed in a tube furnace to separate the silicon solar cells. The conditions were as follows: the temperature was raised to 480°C in a nitrogen environment at a rate of 15°C / min and the residence time was 30 min. After the above pretreatment steps, crystalline silicon cells, copper wires and glass were obtained from the polycrystalline silicon photovoltaic panel, of which 0.5 g of crystalline silicon cells were taken as samples for the following examples and comparative examples.
[0048] Embodiment 1:
[0049] A method for recovering crystalline silicon from waste crystalline silicon solar cells using a deep eutectic solvent-hydrogen peroxide system comprises the following steps:
[0050] Step A, drying choline chloride (ChCl) and oxalic acid (OA) at 65°C under vacuum for 4 hours to remove moisture;
[0051] Step B, the dried ChCl and OA were mixed in a molar ratio of 1:1, placed in an 80°C water bath, and stirred with a magnetic force at a stirring speed of 300 rpm until a uniform transparent liquid was formed to obtain a ChCl-OA DES mixture, which was then cooled to room temperature and stored in a dry container for later use;
[0052] Step C, the DES mixture of step B, hydrogen peroxide with a mass concentration of 30%, and water are mixed to form a DES-H2O2 mixed solution, and then the crystalline silicon cell obtained after pretreatment is mixed with the DES-H2O2 mixed solution, and placed in an 80°C water bath, and magnetic stirring is used at a stirring speed of 300 rpm to fully leach the metal; in this process, the concentration of the DES mixture is controlled to be 2.0 mol / L, the concentration of hydrogen peroxide is controlled to be 2.0 mol / L, the solid-liquid ratio of the crystalline silicon cell and the DES-H2O2 mixed solution is controlled to be 1g / 100ml, and the leaching time is 120 min;
[0053] Step D: After the leaching step is completed, the liquid phase and the solid phase silicon wafer are separated by vacuum filtration; the separated leaching solution is diluted to 100 mL with nitric acid aqueous solution, and then filtered through a 0.22 μm membrane, and the concentrations of metallic silver and aluminum are determined by inductively coupled plasma optical emission spectroscopy (ICP-OES);
[0054] Step E: Dry the separated solid silicon wafer to remove residual moisture, then mix it with 1.0 mol / L NaOH solution, place it in a water bath at 80°C, and stir it with magnetic force at a speed of 300 rpm for 40 min to remove the anti-reflection layer on the front side of the silicon wafer. After filtering, a high-purity silicon wafer with a smooth surface is recovered.
[0055] Embodiment 2:
[0056] A method for recovering crystalline silicon from waste crystalline silicon solar cells using a deep eutectic solvent-hydrogen peroxide system comprises the following steps:
[0057] Step A, drying choline chloride (ChCl) and oxalic acid (OA) at 60 °C under vacuum for 4.5 h to remove moisture;
[0058] Step B, the dried ChCl and OA were mixed in a molar ratio of 1:1, placed in a 75°C water bath, and stirred with a magnetic force at a stirring speed of 350 rpm until a uniform transparent liquid was formed to obtain a ChCl-OA DES mixture, which was then cooled to room temperature and stored in a dry container for later use;
[0059] Step C, the DES mixture of step B, hydrogen peroxide with a mass concentration of 30%, and water are mixed to form a DES-H2O2 mixed solution, and then the crystalline silicon cell obtained after pretreatment is mixed with the DES-H2O2 mixed solution, and placed in a 75°C water bath, and magnetic stirring is used at a stirring speed of 350 rpm to fully leach the metal; in this process, the concentration of the DES mixture is controlled to be 2.5 mol / L, the concentration of hydrogen peroxide is controlled to be 2.0 mol / L, the solid-liquid ratio of the crystalline silicon cell and the DES-H2O2 mixed solution is 1g / 100ml, and the leaching time is 110 min;
[0060] Step D: After the leaching step is completed, the liquid phase and the solid phase silicon wafer are separated by vacuum filtration; the separated leaching solution is diluted to 100 mL with nitric acid aqueous solution, and then filtered through a 0.22 μm membrane, and the concentrations of metallic silver and aluminum are determined by inductively coupled plasma optical emission spectroscopy (ICP-OES);
[0061] Step E: Dry the separated solid silicon wafer to remove residual moisture, then mix it with 1.0 mol / L NaOH solution, place it in a water bath at 80°C, stir it with magnetic force at a speed of 300 rpm, and react for 40 min to remove the anti-reflection layer on the front side of the silicon wafer. After filtering, recover the high-purity silicon wafer with a smooth surface.
[0062] Embodiment 3:
[0063] A method for recovering crystalline silicon from waste crystalline silicon solar cells using a deep eutectic solvent-hydrogen peroxide system comprises the following steps:
[0064] Step A, drying choline chloride (ChCl) and oxalic acid (OA) at 70 °C under vacuum for 3.5 h to remove moisture;
[0065] Step B, the dried ChCl and OA were mixed in a molar ratio of 1:1, placed in an 85°C water bath, and stirred with a magnetic force at a stirring speed of 250 rpm until a uniform transparent liquid was formed to obtain a ChCl-OA DES mixture, which was then cooled to room temperature and stored in a dry container for later use;
[0066] Step C, the DES mixture of step B, hydrogen peroxide with a mass concentration of 30%, and water are mixed to form a DES-H2O2 mixed solution, and then the crystalline silicon cell obtained after pretreatment is mixed with the DES-H2O2 mixed solution, and placed in an 85°C water bath, and magnetic stirring is used at a stirring speed of 250 rpm to fully leach the metal; in this process, the concentration of the DES mixture is controlled to be 2.0 mol / L, the concentration of hydrogen peroxide is controlled to be 1.5 mol / L, the solid-liquid ratio of the crystalline silicon cell and the DES-H2O2 mixed solution is 1g / 125ml, and the leaching time is 130 min;
[0067] Step D: After the leaching step is completed, the liquid phase and the solid phase silicon wafer are separated by vacuum filtration; the separated leaching solution is diluted to 100 mL with nitric acid aqueous solution, and then filtered through a 0.22 μm membrane, and the concentrations of metallic silver and aluminum are determined by inductively coupled plasma optical emission spectroscopy (ICP-OES);
[0068] Step E: Dry the separated solid silicon wafer to remove residual moisture, then mix it with 1.0 mol / L NaOH solution, place it in a water bath at 80°C, and stir it with magnetic force at a speed of 300 rpm for 30 min to remove the anti-reflection layer on the front side of the silicon wafer. After filtering, a high-purity silicon wafer with a smooth surface is recovered.
[0069] Embodiment 4:
[0070] A method for recovering crystalline silicon from waste crystalline silicon solar cells using a deep eutectic solvent-hydrogen peroxide system comprises the following steps:
[0071] Step A, drying choline chloride (ChCl) and oxalic acid (OA) at 65°C under vacuum for 4 hours to remove moisture;
[0072] Step B, the dried ChCl and OA were mixed in a molar ratio of 1:1, placed in an 80°C water bath, and stirred with a magnetic force at a stirring speed of 300 rpm until a uniform transparent liquid was formed to obtain a ChCl-OA DES mixture, which was then cooled to room temperature and stored in a dry container for later use;
[0073] Step C, the DES mixture of step B, hydrogen peroxide with a mass concentration of 30%, and water are mixed to form a DES-H2O2 mixed solution, and then the crystalline silicon cell obtained after pretreatment is mixed with the DES-H2O2 mixed solution, and placed in an 80°C water bath, and magnetic stirring is used at a stirring speed of 300 rpm to fully leach the metal; in this process, the concentration of the DES mixture is controlled to be 2.2 mol / L, the concentration of hydrogen peroxide is controlled to be 1.8 mol / L, the solid-liquid ratio of the crystalline silicon cell and the DES-H2O2 mixed solution is 1g / 110ml, and the leaching time is 120 min;
[0074] Step D: After the leaching step is completed, the liquid phase and the solid phase silicon wafer are separated by vacuum filtration; the separated leaching solution is diluted to 100 mL with nitric acid aqueous solution, and then filtered through a 0.22 μm membrane, and the concentrations of metallic silver and aluminum are determined by inductively coupled plasma optical emission spectroscopy (ICP-OES);
[0075] Step E: Dry the separated solid silicon wafer to remove residual moisture, then mix it with 1.0 mol / L NaOH solution, place it in a water bath at 80°C, and stir it with magnetic force at a speed of 300 rpm for 30 min to remove the anti-reflection layer on the front side of the silicon wafer. After filtering, a high-purity silicon wafer with a smooth surface is recovered.
[0076] The main steps of the following comparative examples are the same as those of Example 1, except that:
[0077] Comparative Example 1 (ChCl-H2O system):
[0078] The dried choline chloride (ChCl) was mixed with water and placed in an 80°C water bath to prepare a 2.0 mol / L choline chloride aqueous solution (ChCl-H2O); then, the 2.0 mol / L ChCl-H2O was mixed with the crystalline silicon cell, placed in an 80°C water bath, and magnetic stirring was used at a stirring speed of 300 rpm to fully leach the metal; in this process, the solid-liquid ratio of the crystalline silicon cell to the ChCl-H2O solution was 1g / 100ml, and the leaching time was 120 min;
[0079] Comparative Example 2 (OA-H2O system):
[0080] The dried oxalic acid (OA) and water were mixed and placed in an 80°C water bath to prepare a 2.0 mol / L oxalic acid aqueous solution (OA-H2O); then, the 2.0 mol / L OA-H2O was mixed with the crystalline silicon cell, placed in an 80°C water bath, and magnetic stirring was used at a stirring speed of 300 rpm to fully leach the metal; in this process, the solid-liquid ratio of the crystalline silicon cell to the OA-H2O solution was 1g / 100ml, and the leaching time was 120 min;
[0081] Comparative Example 3 (DES-H2O system):
[0082] A DES mixture of ChCl-OA and water was mixed to form a DES-H2O mixed solution, and then the crystalline silicon cell was mixed with the DES-H2O mixed solution and placed in an 80 ℃ water bath. Magnetic stirring was used with a stirring speed of 300 rpm to fully leach the metal. In this process, the concentration of the DES mixture was 2.0 mol / L, the solid-liquid ratio of the crystalline silicon cell and the DES-H2O mixed solution was 1g / 100ml, and the leaching time was 120 min.
[0083] The above Examples 1 to 4 and Comparative Examples 1 to 3 were respectively subjected to the following experiments:
[0084] (i) The concentrations of metal Ag and Al in the filtrate after leaching were measured by inductively coupled plasma optical emission spectroscopy (ICP-OES), and the metal leaching efficiency was calculated:
[0085] Metal leaching efficiency η Me Calculated by formula (1):
[0086] η Me = [(C Me × V) / (ω Me × m)] × 100% (1)
[0087] Among them, C Me (mg / L) is the concentration of the metal element (Me is Ag or Al);
[0088] V (L) is the volume of the leachate, i.e., the volume of the filtrate after dilution with the nitric acid aqueous solution (0.1 L);
[0089] ω Me (mg / g) is the concentration of metal Me in the crystalline silicon cell;
[0090] m (g) is the weight of the crystalline silicon cell (0.5 g).
[0091] The leaching efficiency of the metal aluminum and silver in Examples 1 to 4 is shown in Table 2 and Figure 1As shown, under the synergistic effect of DES and H2O2, the leaching efficiency of metallic silver in silicon solar cells reached more than 83%, with a maximum of 89.19%. At the same time, metallic aluminum was also completely leached, with a leaching rate of 100%.
[0092] Table 2. Leaching effects of aluminum and silver in Examples 1 to 4
[0093]
[0094] Example 1 (DES-H2O2 system), Comparative Example 1 (ChCl-H2O system), Comparative Example 2 (OA-H2O system) and Comparative Example 3 (DES-H2O system) were selected to verify the leaching efficiency of metallic silver and aluminum after the crystalline silicon cell samples were treated with different mixed solution systems. The comparison results are shown in Table 3 and Figure 2 (a) shows:
[0095] Table 3. Leaching effects of aluminum and silver in Example 1, Comparative Examples 1 and 2
[0096]
[0097] From Table 3 and Figure 2 (a) It can be seen that under the same leaching experimental conditions, in the ChCl-H2O system of Comparative Example 1, the leaching efficiency of metallic silver is only 0.39%, and the leaching efficiency of aluminum is also very low, only 2.31%; in the OA-H2O system of Comparative Example 2, the leaching efficiency of silver is also close to 0, while the leaching efficiency of aluminum reaches 100%, indicating that oxalic acid (OA) is the main active species for aluminum leaching; although Comparative Example 3 also uses ChCl-OA DES, in the DES-H2O system using only DES, the leaching efficiency of metallic silver is only 45.17%; compared with the above three comparative examples, in the DES-H2O2 system of Example 1, under the synergistic effect of DES and H2O2, the leaching efficiency of silver is increased to 89.19%, which is almost twice the silver leaching effect of Comparative Example 2. Therefore, the ChCl-OA DES and H2O2 of the present invention both play an important role in the silver leaching process. From Tables 3 and Figure 2(a) It can be seen that under the same leaching experimental conditions, in the ChCl-H2O system of Comparative Example 1, the leaching efficiency of metallic silver is only 0.39%, and the leaching efficiency of aluminum is also very low, only 2.31%; in the OA-H2O system of Comparative Example 2, the leaching efficiency of silver is also close to 0, while the leaching efficiency of aluminum reaches 100%, indicating that oxalic acid (OA) is the main active species for aluminum leaching; although ChCl-OA DES is also used in Comparative Example 3, the leaching efficiency of metallic silver is only 45.17% in the DES-H2O system using only DES; compared with the above three comparative examples, in the DES-H2O2 system of Example 1, under the synergistic effect of DES and H2O2, the leaching efficiency of silver is increased to 89.19%, which is almost twice the silver leaching effect of Comparative Example 2. Therefore, the ChCl-OA DES and H2O2 of the present invention both play an important role in the silver leaching process.
[0098] Experiment on the mechanism of metallic silver leaching
[0099] 1. Compare the initial pH values of different solution systems
[0100] The initial pH values of the solution systems of Example 1, Comparative Example 2 (Comparative Examples 1 and 2 are both single solution systems, one of which is selected as a representative) and Comparative Example 3 are measured respectively.
[0101] First, the existence of ChCl-OA DES is not just a simple combination of two components, ChCl and OA, but the two are closely connected through hydrogen bonding, which reduces the melting point of the components and increases their solubility, which will affect the acidity of the DES aqueous solution and thus affect the leaching of metallic silver. That is, OA is miscible with water in any ratio in DES, thereby increasing the solubility of OA, thereby increasing the acidity of the system, and promoting the direct leaching of silver in DES;
[0102] Oxalic acid (OA) is a dibasic organic weak acid, and its ionization process is divided into two steps (Formula 1 and Formula 2). The synthesis of DES increases the degree of ionization of oxalic acid. After adding H2O2, H + The degree of ionization is further enhanced.
[0103] H2C2O4 → H + (aq) + HC2O4 - (aq) (first step ionization) (1)
[0104] HC2O4 - → H + (aq) + C2O4 2- (aq) (Second step ionization) (2)
[0105] By measuring the initial pH values of three different solution systems of Comparative Example 2, Comparative Example 3 and Example 1, the results are as follows: Figure 2 As shown in (b), the initial pH values of the three solution systems are -0.52, -0.88, and -1.05, respectively, that is, the acidity of the three solution systems of Comparative Example 2, Comparative Example 3, and Example 1 is gradually enhanced; this proves that the synthesis of ChCl-OA DES increases the degree of ionization of OA, thereby increasing the acidity of the system and promoting the direct leaching of silver in DES.
[0106] 2. Strengthening effect of H2O2 in DES-H2O2 system
[0107] Hydrogen peroxide (H2O2) is an active oxidant that releases superoxide free radicals (·O2 - ) and silver ions (see formula 3). Through free radical capture experiments, such as Figure 2 (c) shows that the decomposition of H2O2 is accompanied by superoxide radicals (·O2 - )’s production.
[0108] According to the production process of the polycrystalline silicon photovoltaic panel used in the present invention, the metallic silver in the silver electrode is in the form of micrometers, and the process involves nanometer-scale reactions. Since the leaching efficiency of Examples 1 to 4 is high, the silver on the silicon wafer is removed very cleanly after treatment and cannot be observed. Therefore, the silicon wafer obtained after treatment of Comparative Example 3 with poor leaching efficiency is selected, and the electron microscope image of its front surface is taken, as shown in FIG. Figure 7 As shown, the nanoscale reaction can be reflected. This will lead to size effect and surface effect, that is, nanosilver has a large specific surface area, which can provide more active sites, thereby accelerating the release of silver ions. The leaching of silver is an oxidation process. Under the catalysis of H2O2, silver will be directly oxidized, while the activation energy of silver leaching in H2O2 is reduced;
[0109] In addition, due to the lower pH value of the DES-H2O2 system, the highly oxidative superoxide radicals (·O2 - ) has higher activity under acidic conditions. Silver ions react with hydrogen ions (H + ) and superoxide radicals (·O2 - ) will enhance the oxidation, thereby producing a stronger oxidizing environment, further increasing the oxidation rate of silver and accelerating the leaching process of silver (see Formula 4 and Formula 5).
[0110] Ag + 2H2O2 → Ag + + ·O2 - + 2H2O (3)
[0111] 3Ag + 3H2O2 + 2H+ → 3Ag + + ·O2- + 4H2O (4)
[0112] 3Ag + 4H + + ·O2- → 3Ag + + 2H2O (5)
[0113] 3. Complexation of Ag in DES system
[0114] Silver is a typical transition metal with an unoccupied d orbital. The unpaired electrons of the keto oxygen make oxalic acid a suitable ligand and react with metals and Cl - Formation of complex. Ag + The four electron orbitals of 5s5p are all empty. Carboxylates can be used as ligands of silver to form complexes, in which two silvers are bridged with two carboxylates as central ions. There are free chloride ions in choline chloride in the DES system, which can usually precipitate with silver ions in the form of silver chloride. When the concentration of chloride ions is high, anti-dissolution occurs. When carboxylate ions and chloride ions exist at the same time, a disilver complex is formed. Therefore, the complex formed may contain two silvers as central ions to coordinate two carboxylate ions and two chloride ions.
[0115] The present invention simulates the leaching process of metallic silver in DES by using AgNO3+DES. Example 1 is selected, and the negative ion mode spectrum of DES high-resolution mass spectrometry after silver leaching (see Figure 3 ), several possible configurations of silver complex intermediates were speculated, including [(Ag + )(OH - )(Cl - )] - , [(HC2O4 - )2(Ag + )2(Cl - )2] 2- ·3H2O and [(ChCl)(HC2O4 - )(Ag + )(Cl - )] - , these silver complexes involve complexation between silver ions, oxalate ions, and chloride ions.
[0116] From this, we can deduce the following process of silver complex formation: after silver is leached, it first complexes with chloride ions in the system. Further, based on the formation of the complex, the two may further complex with oxalic acid to form a composite complex. The specific reaction process is as follows:
[0117] Ag + + H2O + Cl - ⇌ [(Ag + )(H2O)(Cl - )] (6-1)
[0118] [(Ag + )(H2O)(Cl - )] ⇌ [(Ag + )(OH - )(Cl - )] - + H + (6-2)
[0119] H2C2O4 ⇌ HC2O4 - + H + (6-3)
[0120] Ag + + HC2O4 - + 2ChCl ⇌ [(ChCl)(HC2O4 - )(Ag + )(Cl - )] - + Ch + (6-4)
[0121] Ag + + HC2O4 - + Cl - + 3H2O ⇌ [(HC2O4 - )2(Ag + )2(Cl - )2] 2- ·3H2O (6-5)
[0122] In summary, the main reasons why silver has a higher leaching efficiency in the DES-H2O2 system are: (1) oxalic acid (OA) is miscible with water in the DES mixture at any ratio, and the solubility of oxalic acid increases, thereby increasing the acidity of the system, thereby promoting the direct leaching of silver in DES; (2) under the catalytic action of H2O2, silver is directly oxidized accompanied by superoxide radicals (·O2 - ) is generated. The oxidizing property of free radicals in an acidic environment is stronger, which reduces the activation energy of silver leaching in H2O2 and further promotes the leaching of silver. (3) After the silver ions are generated, the oxalate and chloride ion ligands in the DES-H2O2 system form complexes with them, further promoting the forward leaching of silver.
[0123] (III) Performance testing of recycled silicon wafers
[0124] In the DES-H2O2 system, the silver strip on the front side of the crystalline silicon cell sample and the aluminum electrode layer on the back side have been removed. In order to obtain a higher purity silicon wafer, NaOH solution is finally used to remove the remaining impurity layer (mainly Si3N4). The chemical reaction between Si3N4 and NaOH is shown in the following formula 7:
[0125] Si3N4 + 6NaOH + 3H2O→3Na2SiO3 + 4NH3↑ (7)
[0126] As the impurities are removed, the silicon wafer gradually returns to its original thickness. In order to obtain the element content on the surface of the silicon wafer, the silicon wafer obtained after the treatment in Example 1 was selected and tested by scanning electron microscopy-electron energy spectrum and XPS spectrum. The results are as follows: Figure 4 As shown. Figure 4 (a) It can be seen that the element content at each point on the silicon wafer surface shows a similar composition, with an average silicon content of 97.47 wt%. Due to the inevitable oxidation of the silicon wafer surface, a small amount of O (about 2wt%) was detected. It is worth noting that the second point is located in the groove of the silver bar, but no silver was detected, which shows that the DES-H2O2 system has a high efficiency in leaching silver; as shown in Figure 4 (bd), the XPS spectrum of the silicon wafer surface provides the same evidence. The peak observed at 102.4eV of the Si2p orbital corresponds to the Si of the Si3N4 layer. 2+ or Si 3+ When Si3N4 is removed, Si is exposed and its corresponding peak can be observed at 98.7 eV. The disappearance of the peak at 397.8 eV belonging to Si3N4 on the N1s orbital means that Si3N4 has been removed.
[0127] The surface details of the silicon wafer after the impurity Si3N4 was removed were observed using an electron microscope, the thickness of the battery was measured using a digital micrometer (with an accuracy of one thousandth), and the N content was determined based on the energy spectrum of the scanning electron microscope. By the above methods, the battery thickness and N content of the crystalline silicon battery sample before and after the treatment of Example 1 were measured, and the results are as follows: Figure 5As shown in Figure 5a, the average measured thickness of the crystalline silicon cell sample before treatment was 223 μm, and the thickness of the silicon wafer after removing the electrode metal was reduced to 183 μm. The thickness of the silicon wafer obtained after treatment in Example 1 was 169 μm, and the silicon retention rate was 99.41%. As can be seen from Figure 5b, the N content of the silicon wafer before treatment and the recycled silicon wafer was compared, and the N content of the front surface decreased by 96% (from 11.37% to 0.37%). After DES-H2O2-NaOH treatment, both sides of the silicon wafer showed a metallic luster and the appearance of polycrystalline silicon.
[0128] 4. DES reusability experiment
[0129] The reusability of DES was investigated through a cycle experiment. Taking Example 1 as an example, after the metal leaching reaction was completed, the DES solution was collected and slowly stirred and evaporated in a water bath at 80°C to evaporate and remove the water therein. After three cycles, the changes in the DES structure were detected by FT-IR (Fourier transform infrared spectroscopy) and 1H NMR (nuclear magnetic resonance hydrogen spectroscopy). The results are as follows: Figure 6 shown. Figure 6 The FT-IR spectrum of a shows 3750-3000 cm -1 This corresponds to the OH stretching vibration of OH-Cl in DES, 1617 and 1220 cm -1 The peaks corresponding to C=O and CO vibrations at the bottom of the graphene crystals became smaller, indicating that oxalic acid was consumed in the process. 1H NMR also showed the same result (see Figure 6b). After silver was leached and complexes were formed, the electron cloud density of hydrogen decreased and the chemical shift (δ) increased. After multiple uses, the characteristics of DES did not change much, indicating that it has the potential for reuse.
[0130] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.
Claims
1. A method for recovering crystalline silicon from waste crystalline silicon solar cells using a deep eutectic solvent-hydrogen peroxide system, characterized in that: The following steps are involved: Step A, vacuum drying choline chloride and oxalic acid to remove moisture; Step B, mixing the dried choline chloride and oxalic acid in a molar ratio of 1:1, placing in a water bath, controlling the temperature at 75-85° C., and stirring in the water bath until a uniform transparent liquid is formed to obtain a choline chloride-oxalic acid DES mixture, then cooling to room temperature, and storing in a dry container for standby use; Step C, mixing a certain amount of the DES mixture of step B, hydrogen peroxide with a mass concentration of 30%, and water to form a DES-H2O2 mixed solution, and then mixing the crystalline silicon cell obtained after pretreatment with the DES-H2O2 mixed solution, and placing them in a water bath, controlling the temperature at 75-85°C, and stirring for a period of time to fully leach the metal; Step D: After the leaching step is completed, the liquid phase and the solid phase silicon wafer are separated by vacuum filtration, the concentrations of metallic silver and aluminum in the separated leaching solution are measured, and the metal leaching rate is calculated; Step E: The separated solid silicon wafer is first dried to remove residual moisture, then mixed with NaOH solution, and placed in a water bath at 75-85° C. with constant stirring to remove the anti-reflection layer on the front side of the silicon wafer. After filtration, a high-purity silicon wafer with a smooth surface is recovered.
2. The method for recovering crystalline silicon from waste crystalline silicon solar cells using a deep eutectic solvent-hydrogen peroxide system according to claim 1, characterized in that: In step A, the vacuum drying temperature is 60-70°C and the drying time is 3.5-4.5 h.
3. The method for recovering crystalline silicon from waste crystalline silicon solar cells using a deep eutectic solvent-hydrogen peroxide system according to claim 1, characterized in that: In steps B and C, magnetic stirring is used in a water bath at a stirring speed of 250 to 350 rpm.
4. The method for recovering crystalline silicon from waste crystalline silicon solar cells using a deep eutectic solvent-hydrogen peroxide system according to claim 1, characterized in that: In step C, in the DES-H2O2 mixed solution, the concentration of the DES mixture is 2.0-2.5 mol / L, the concentration of hydrogen peroxide is 1.5-2.0 mol / L, the solid-liquid ratio of the waste crystalline silicon cell to the DES-H2O2 mixed solution is 1g / 100ml-1g / 125ml, and the leaching time is 110-130 min.
5. The method for recovering crystalline silicon from waste crystalline silicon solar cells using a deep eutectic solvent-hydrogen peroxide system according to claim 1, characterized in that: In step C, the crystalline silicon cell is obtained by pre-processing the crystalline silicon photovoltaic panel, and the pre-processing step is: First, remove the aluminum frame and junction box of the crystalline silicon photovoltaic panel, then cut the battery pack, and then perform pyrolysis in a tubular furnace. The pyrolysis conditions are: heating to 480 °C in a nitrogen environment, at a rate of 15 °C / min, and a residence time of 30 min; after pyrolysis, crystalline silicon cells, copper wires and glass are obtained.
6. The method for recovering crystalline silicon from waste crystalline silicon solar cells using a deep eutectic solvent-hydrogen peroxide system according to claim 1, characterized in that: In step D, the separated leaching solution is diluted to 100 mL with aqueous nitric acid solution, and then filtered through a 0.22 μm membrane. The concentrations of metallic silver and aluminum are determined by inductively coupled plasma emission spectroscopy, and the leaching efficiencies of metallic silver and aluminum are calculated.
7. The method for recovering crystalline silicon from waste crystalline silicon solar cells using a deep eutectic solvent-hydrogen peroxide system according to claim 6, characterized in that: Metal leaching efficiency η Me Calculated by formula (1): or Me = [(C Me × V) / (ω Me × m)] × 100% (1) Among them, C Me is the concentration of the metal element, the unit is mg / L, the metal element Me is Ag or Al; V is the volume of the leachate, in L; ω Me It is the concentration of metal Me in the crystalline silicon cell, in mg / g; m is the weight of the crystalline silicon cell, in g.
8. The method for recovering crystalline silicon from waste crystalline silicon solar cells using a deep eutectic solvent-hydrogen peroxide system according to claim 1, characterized in that: In step E, the concentration of the NaOH solution is 1.0 mol / L, and the reaction time is 30-40 min.
9. The method for recovering crystalline silicon from waste crystalline silicon solar cells using a deep eutectic solvent-hydrogen peroxide system according to claim 1, characterized in that: In step E, magnetic stirring is used in a water bath, and the stirring speed is 250 to 350 rpm.
Citation Information
Patent Citations
Crystalline silicon solar cell resource classifying recycling method
CN107457250A